2007
DOI: 10.1097/01.bsd.0000211291.21766.4d
|View full text |Cite
|
Sign up to set email alerts
|

The Use of C1 Lateral Mass Screws in Complex Cervical Spine Surgery: Indications, Techniques, and Outcome in a Prospective Consecutive Series of 25 Cases

Abstract: On the basis of our experience, proficiency with the use of C1-LMS screw fixation greatly enhances the ability to manage complex atlantoaxial or craniocervical pathologies with low morbidity. This technique should be considered an excellent adjunct or alternative to transarticular screw fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 30 publications
1
57
0
1
Order By: Relevance
“…Harms construct also has biomechanically superior or at least equivalent stability in comparison with transarticular screw fixation on the all dimensions of motion 4,10,13) . C2 pedicle screw insertion has the lower risk of vertebral artery injury than transarticular screw placement 7,8) . Additionally, C1LM-C2P screw fixation requires smaller incision than transarticular screw fixation due to more vertical trajectory to the axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harms construct also has biomechanically superior or at least equivalent stability in comparison with transarticular screw fixation on the all dimensions of motion 4,10,13) . C2 pedicle screw insertion has the lower risk of vertebral artery injury than transarticular screw placement 7,8) . Additionally, C1LM-C2P screw fixation requires smaller incision than transarticular screw fixation due to more vertical trajectory to the axis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Goel and Laheri 5) have first described a method of C1-C2 fixation using a plate-screw system for the C1LM and C2P as an alternative to transarticular screw fixation in 1994. Furthermore, Harms and Melcher 8) modified Goel's technique using a polyaxial screw-rod construct in 2001 and this approach is widely adopted by many surgeons [7][8][9]11) . C1LM-C2P fixation has advantages over the transarticular screw fixation technique.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there is a large body of literature concerning techniques, indications and union rates in C2-fractures [72], but data regarding the most important outcome measure, the functional and clinical outcome, are scant [24,68]. Currently, in addition to nonsurgical treatment including semirigid collars or the Halo-thoracic-vest (HTV), contemporary surgical techniques for the treatment of C2-fractures include anterior odontoid screw fixation (AOSF) [2,62], posterior and anterior transarticular screw fixation C1-2 [51], C1-lateral mass and C2-Isthmus/lamina fixation [32] and plated anterior discectomy and fusion for the unstable Hangman's fracture (Hmfx) [46,83]. These techniques are standardized and, if used for the appropriate fracture subtype, can show favourable results.…”
Section: Introductionmentioning
confidence: 99%
“…Harms et al 10) and Goel et al 7) reported 100% bony fusion without VA injury or spinal cord violation using C1LM-C2P screw fixation. Additionally, in a previous paper by Gunnarsson et al 9) , it was reported that C2 pedicle screw insertion had a lower rate of VA injury than TAF.…”
Section: • Acknowledgementsmentioning
confidence: 99%